Diseño de branding e identidad visual Agro Minerva - Martinez Argueta, Ana Cecilia; Martínez Martínez, Hilda María; Vasquez Castro, Hasiel Adonay (Universidad de El Salvador, 2025)
Titulo: Diseño de branding e identidad visual Agro Minerva